Rapid mechanical stimulation of inner-ear hair cells by photonic pressure - Abeytunge, Sanjeewa; Gianoli, Francesco; Hudspeth, A. James; Kozlov, Andrei S. (Dryad, 2021)
Hair cells, the receptors of the inner ear, detect sounds by transducing
mechanical vibrations into electrical signals. From the top surface of
each hair cell protrudes a mechanical antenna, the hair bundle, which the
cell uses to detect and amplify auditory stimuli, thus sharpening
frequency selectivity and providing a broad dynamic range. Current methods
for mechanically stimulating hair bundles are too slow to encompass the
frequency range of mammalian hearing and are plagued by inconsistencies.
To overcome these challenges, we have developed a method to move
individual hair bundles with photonic force. This technique uses an
optical fiber whose tip is tapered to a diameter of a few micrometers and
endowed with a ball lens to minimize divergence of the light beam. Here we
describe the fabrication, characterization, and application of this
optical system and demonstrate the rapid application of photonic force to
vestibular and cochlear hair cells.
Data were collected as described in the manuscript.
Each dataset corresponds to a different figure. The data are saved in .txt
files where the columns are time, laser redout and photodiode
measurements. The traces reported in the manuscript are averages
over 25 repetitions and the uploaded files contain
every trace. The .log files contain all other
relevant information: stimuls type, duration, delay, intensity of the
laser, outputs, range of frequencies, et cetera. The file
"Data_Fig5_Histogram.txt" includes the Time, X
position, Y position and Vector X+Y of the hair bundle oscillations before
and after laser irradiation used to compose the histogram in Figure
5.
Keywords: FOS: Natural sciences